License Plate Recognition and Extraction of Details from Database - Haarathi, P.; Subbaiah, G. Venkata; Nandini, P. Hema; Naveena, P. Bala (Leading the Charge: A Guide to Management, Entrepreneurship and Technology in the Dynamic Business Landscape Edition 1, 2025)
A sort of technology known as number plate recognition (LPR), primarily software, allows computer systems to automatically read a car's number plate number from digital photos. License Plate Recognition systems use the concept of optical character recognition to read the characters on vehicle license plates. Registration plate detection devices rely on optical character processing to comprehend the written information on the automobile's registration tag. Stated differently, LPR produces the characters that are engraved on an automobile's registration plate after receiving an image of the vehicle as input. It displays the vehicle's details and reads the characters. It can make use of already-installed closed-circuit television, and traffic enforcement cameras. It is used by enforcement agencies across the globe to enforce the law, including Figuring out whether an automobile is licensed or registered. On top of that, this is the case utilized by highway agencies and other pay-per-use roadways for electronic toll collecting and traffic flow cataloging. The main motive is to interpret and show registration plate individuals so that cars may be recognized and categorized.